AB0978 Comparison of effectiveness and safety of tramadol/acetaminophen and non-steroidal anti-inflammatory drugs (NSAIDS) for treatment of knee osteoarthritis in elderly patients. (23rd January 2014) - Hur, J.-W.; Ryou, J.W.; Kim, S.Y.
Abstract : Background: The use of a combination of oral analgesics vs. an individual agent offers several potential benefits. Combining analgesics into a single product may facilitate prescribing and compliance by reducing the total number of medications that a patient must take to manage pain. Furthermore elderly patients usually have risk of bleeding and other complications. Objectives: To compare the analgesic effectiveness and safety of tramadol 37.5mg/acetaminophen 325mg combination tablets(tramadol/acetaminophen) with non-steroidal anti-inflammatory drugs (NSAIDs) for treatment of osteoarthrits in elderly patients. Methods: This randomized controlled study enrolled 48 patients with chronic knee osteoarthritis that diagnostic period was over 3 months. Patients with at least moderate pain [visual analog scale (VAS) with scores ≥40/100 mm] after washout period were randomized to tramadol/acetaminophen or NSAID. All patients received tramadol/acetaminophen 1 tablet TID or NSAID (naproxen 500mg) BID. Primary outcome measure was final pain VAS score. Secondary measures included pain relief (5 point Likert scale), adverse events, and overall medication assessments. Results: In total, 43 intent-to-treat (ITT) patients received tramadol/acetaminophen (n=21) or NSAID (n=22). Mean baseline pain VAS scores were not difference between two groups. ITT analysis showed significantly better mean final VAS scores (38.45 vs 31.24, p=0.004) and mean final pain relief scores (2.18 vs 2.95; p=0.007) for tramadol/acetaminophen than for NSAID. The most common treatment related adverse events with tramadol/acetaminophen were nausea/vomiting (47.6%) and constipation (33.3%). Epigastric soreness and heartburn was more frequent in NSAID treatment. Conclusions: Tramadol/acetaminophen combination showed better effectiveness in pain reduction compared with NSAIDs used for the treatment of osteoarthritis in elderly patients. References: Tramadol/acetaminophen combination tablets and codeine/acetaminophen combination capsules for the management of chronic pain: A comparative trial. Clinical Therapeutics. 2001;23:1429-45. Efficacy and safety of tramadol HCl in breakthrough musculoskeletal pain attributed to osteoarthritis. J Rheumatol. 1998;25:1358-63. Disclosure of Interest: None Declared